2015
DOI: 10.14202/vetworld.2015.482-486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-carnitine supplementation on growth performance, nutrient utilization, and nitrogen balance of broilers fed with animal fat

Abstract: Aim:This experiment was conducted to evaluate the effect of L-carnitine supplementation on growth performance, nutrient utilization and nitrogen balance in broilers fed with animal fat.Materials and Methods:80 day-old Cobb commercial broiler chicks were randomly assigned into two dietary treatment groups with four replicates of ten chicks each. The diets were isonitrogenous and isocaloric. The birds in both the control (T1) and treatment group (T2) were fed with a diet having 5% animal fat, while the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…This may be due to ducklings are able to compensate their feed intake according to their energy requirements as well as the experimental diet had similar metabolizable energy. This result is similar with Murali et al (2015) who reported that dietary LC addition (900 mg/kg diet) did not affect feed consumption in broilers during growing period (0-6 wks). Also, Awad et al (2016) reported that FC for Domyati ducklings was not significantly affected due to LC supplementation with 150up to 600 mg/kg diet.…”
Section: Resultssupporting
confidence: 92%
“…This may be due to ducklings are able to compensate their feed intake according to their energy requirements as well as the experimental diet had similar metabolizable energy. This result is similar with Murali et al (2015) who reported that dietary LC addition (900 mg/kg diet) did not affect feed consumption in broilers during growing period (0-6 wks). Also, Awad et al (2016) reported that FC for Domyati ducklings was not significantly affected due to LC supplementation with 150up to 600 mg/kg diet.…”
Section: Resultssupporting
confidence: 92%
“…A decreased level of glucose in the blood of broilers with the introduction of tannic acid into the diet was observed in earlier studies [ 32 ], as well as triglycerides on feeding an essential oil mix obtained from plants [ 33 ]. It is known that triglycerides are important energy products, especially those used by chickens for growth [ 34 , 35 ]. In addition, a recent study [ 36 ] found that bifidobacteria inhibit fat accumulation, improve insulin resistance, and reduce blood glucose levels in the blood of laboratory animals.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Takahashi, Kitano, and Akiba () did not observe an effect of supplemental L‐carnitine (experiment 1: 0, 100 and 3,000 mg/kg diet; experiment 2: 0 and 100 mg/kg diet) fed for 24 days on BW gain, feed intake and gain‐to‐feed ratio in Ross broiler chickens (experiment 1: n = 48; experiment 2: n = 40), whereas the authors could demonstrate that supplemental L‐carnitine enhances concanavalin A‐stimulated splenic mononuclear cell proliferation in broiler chickens. Finally, Murali, George, Ally, and Dipu (), which evaluated the effect of a high dietary L‐carnitine concentration (900 mg/kg diet) on performance of mixed‐sex Vencobb broiler chickens ( n = 80) in a 6‐week feeding trial and on nutrient utilization and nitrogen balance in a subsequent metabolism trial of 3‐day duration, found no effect of supplemental L‐carnitine on BW, feed consumption and gain‐to‐feed ratio in the starter, finisher and whole period. In addition, nutrient utilization and nitrogen balance estimated from the metabolism trial did not indicate any effect of supplemental L‐carnitine.…”
Section: Efficacy Of L‐carnitine Supplementation On Performance Of Momentioning
confidence: 99%